Prevalence, Characteristics, and Correlates of Fatigue in Indian Breast Cancer Survivors: A Cross-Sectional Study - Kaur, Navneet; Mahapatra, Puneet Prasan; Chakraborty, Sagar (South Asian Journal of Cancer, 2022)
Background Fatigue is one of the commonest sequelae of breast cancer treatment that adversely impacts quality of life (QOL) of breast cancer survivors (BCSs). However, very limited data are available about cancer-related fatigue in Indian patients. Hence, this study was planned with the objectives to study (1) prevalence of fatigue in short-, intermediate-, and long-term follow-up; (2) severity and characteristics of fatigue; (3) impact of fatigue on QOL; and (4) correlation of fatigue with other survivorship issues.Materials and Methods The study was conducted on (n = 230) BCSs who had completed their primary treatment (surgery, radiotherapy, and chemotherapy) and were coming for follow-up. The prevalence of fatigue was noted from a screening tool, which comprised of 14 commonly reported survivorship issues. Assessment of fatigue was done by using survivorship fatigue assessment tool-1 score and QOL was assessed by functional assessment of cancer therapy-breast (FACT-B) questionnaires. To understand how fatigue evolved over time, survivors were divided into three groups according to the time elapsed since initial treatment: Group 1: <2 years (n = 105); Group 2: 2–5 years (n = 70); Group 3: >5 years (n = 55).Statistical Analysis Data was analyzed by using simple descriptive statistics, one way analysis of variance followed by Tukey's test for comparison of quantitative data among the three groups, and Pearson correlation coefficients for association of fatigue with other survivorship issues.Results Clinically significant fatigue (≥4) was noted in 38% of BCSs. However, high overall prevalence of fatigue (60%) was seen, which persisted in long-term survivors (51%) as well. Severity of fatigue was mostly mild (37.7%) to moderate (47.1%). Fatigue scores were significantly higher in short-term survivors (5.01 ± 2.06) than intermediate- (4.03 ± 1.42) and long-term BCSs (3.57 ± 1.37). The mean score on FACT-B was 90.07 ± 10.17 in survivors with fatigue and 104.73 ± 7.13 in those without fatigue (p = 0.000). Significant correlation of fatigue was seen with other survivorship issues like limb swelling, chronic pain, premature menopause, and its related symptoms and emotional distress.Conclusion Fatigue is highly prevalent in BCSs. Survivorship care programs should include appropriate measures to evaluate and address fatigue.
Keywords: breast cancer survivors; fatigue; quality of life; survivorship care